Analisis Nilai-nilai Multikultural Dalam Novel Assalamualaikum Beijing Karya Asma Nadia - Fatmawati, Weni; Lubis, Ramadhan Saleh; Sinaga, Fitri Juniati; Sipayung, Ratnauli; Deratih M, Wilda (Jurnal Genre (Bahasa, Sastra, dan Pembelajarannya), 2019)
This research is entitled Analysis of Multicultural Values in the novel Assalamualaikum Beijing. This study aims to (1) know multicultural values (2) describe the multicultural values contained in the novel Assalamualaikum Beijing. The main data source in this study is the Assalamualaikum Beijing novel published in 2013 by Asma Nadia with a thick 360-page book. The novel was chosen because the content of the story presented was very interesting giving fresh meaning to the state of multicultural value difference in Beijing with in Indonesia. The focus of this study is related to Multicultural values found in the Assalamualaikum Beijing novel. The research method used is a qualitative descriptive method. Data collection techniques used in this study are using library techniques and content analysis (analysis content). The results of this study are aimed at the public that the multicultural values contained in the Assalamualaikum Beijing novel include values of tolerance, democratic values, religious values, and cultural values. The researcher conducts this research with the aim that the public realize the importance of multiculturalism values such as tolerance values, democratic values, religious values, and cultural values applied in life.